TRANSPORT TIZIMIDA LOGISTIK XIZMATLAR BOZORINING SHAKILLANISHI TARIXI (Marketing Journal, 2026)
AbstractThis article examines the formation of the logistics services market within thetransport system, its historical stages, and current development trends. The role oftransport and logistics activities in the economy is analyzed, including the integrationof freight and passenger transportation and the development of multimodal transport systems. Special attention is given to the evolution of logistics intermediaries, freightforwarding services, and the impact of digitalization on market efficiency. The studyalso highlights the modernization of Uzbekistan’s transport system, the developmentof logistics centers, and improvements in service quality. The findings contribute tostrengthening the competitiveness of the national transport system and enhancing theefficiency of the logistics services market.Keywords: cargo delivery system, transport services market, cargo turnover,passenger turnover, transport integration, cargo transportation process, high-techvehicles, transport systems of countries, international relations.